PENGARUH TERPAAN PEMBERITAAN PUAN MAHARANI DI KOMPAS.COM TERHADAP CITRA POLITIK PUAN MAHARANI DAN DAMPAKNYA PADA ELEKTABILITAS PUAN MAHARANI SEBAGAI BAKAL CAPRES - Hasan Hendratmoko; Lintang Ratri Rahmiaji; Adi Nugroho (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
One of the products of news coverage in the mass media is politics. Political news in the media provides information about politics and can help the public in understanding and monitoring the political process in this country. During the period from January to December 2022, the online news portal Kompas.com often highlighted the Chairperson of the Indonesian House of Representatives, Puan Maharani, due to her policies that attracted public attention. At that time, there was also a lot of news coverage about political candidates who would participate in the political contest in 2024. Puan Maharani herself was said to be participating in that political event. However, with the news coverage on the Kompas.com portal that attracted public attention, it can shape the public's perception of her political image, which will affect her electability as a potential presidential candidate. This study aims to determine the influence of news exposure to Puan Maharani on Kompas.com on her political image and its impact on her electability as a potential presidential candidate. The theories used in this study are the Uses and Effects theory and the S-O-R (Stimulus-Organism-Response) theory. The testing was conducted using simple regression analysis and non-probability sampling technique. This study used a sample of 100 people with the characteristics of age between 17-40 years, exposed to news about Puan Maharani on Kompas.com, and residing in Central Java, especially in one of the 17 cities/regencies where the PDI-P won the regional elections in Central Java at 2020, including Semarang, Boyolali, Grobogan, Kebumen, Sragen, Wonosobo, Solo, Klaten, Sukoharjo, Demak, Pekalongan, Wonogiri, Semarang, Purbalingga, Rembang, Blora, and Pekalongan. The results of the study indicate that the exposure to news about Puan Maharani on Kompas.com (X) and Puan Maharani's political image (Z) have a significance value of 0.197, which means it is not significant. Furthermore, Puan Maharani's political image (Z) and her electability as a potential presidential candidate (Y) have a significance value of 0.000, which means it is highly significant, with a correlation coefficient of 0.618. This value indicates that the relationship between the independent variable (Puan Maharani's political image) and the dependent variable (Puan Maharani's electability as a potential presidential candidate) is 0.618 (61.8%) and shows a positive influence between the two variables.